Studying the intra and intermolecular processes of biomolecules using two dimensional infrared spectroscopy - Tiemessen, David (2021)
This Thesis focuses on using ultrafast time-resolved infrared spectroscopy and two-dimensional infrared spectroscopy (2D-IR) for determining the structure and dynamics of a system. Chapter 1 gives an introduction to 2D-IR spectroscopy which is a technique that involves vibrationally exciting a sample, with an initial IRpump pulse, then after a waiting time the sample is probed using an IRprobe pulse. A spectrum is obtained by scanning the frequency of the IRpump pulse at a fixed waiting time. This technique allows the multiple transitions to be probed and valuable information (e.g. the coupling of vibrational modes) such as how energy is transferred, both within a molecule and to its environment, to be elucidated.